Effects of long-term fertilizer practices on rhizosphere soil ammonia oxidizer community structure under the double-cropping rice field - Haiming Tang; Li Wen; Lihong Shi; Kaikai Cheng; Geng Sun; Mei Sun; Weiyan Li (Scientific Reports)
Abstract Ammonia oxidation plays a vital role in regulating soil nitrogen (N) cycle in agricultural soil, which is significantly influenced by different fertilizer regimes. However, there is still need to further investigate the effects of different fertilizer managements on rhizosphere soil ammonia-oxidizing archaea (AOA) and bacteria (AOB) community in the double-cropping rice field. Therefore, the effects of different long-term (37 years) fertilizer managements on rhizosphere soil potential nitrification activity (PNA), AOA and AOB community structure, and its relationship under the double-cropping rice system in southern of China were studied in the present paper. The field experiment included without fertilizer input as a control (CK), inorganic fertilizer (MF), rice straw and inorganic fertilizer (RF), 30% organic manure and 70% inorganic fertilizer (OM). This result indicated that rhizosphere soil organic carbon (SOC) (SOC), total N and ammonium N (NH4 +-N) contents in paddy field with RF and OM treatments were increased. Rhizosphere soil PNA, potential nitrification rate (PNR) and abundance of AOB in paddy field with MF treatment were increased, and abundance of AOA in paddy field with RF and OM treatments were increased, respectively. The result also showed that rhizosphere soil diversity index of AOA and AOB with RF and OM treatments were enhanced, compared with CK treatment. Rhizosphere soil AOB and AOA community composition was dominated by Proteobacteria, Actinobacteria and Acidobacteria with all fertilizer treatments. There had significantly positively correlation between the abundance of AOA and SOC, total N, and NH4-N contents. However, there had significantly negatively correlation between soil pH and abundance of AOA, soil PNA, PNR. As a result, long-term application of rice straw and organic manure was benefit for increasing community structure of rhizosphere soil ammonia oxidizer under the double-cropping rice system in southern of China.